Adsorption and reactions of CH2Br2 on TiO2: Effects of H2O and O2. (2004) - Chen, Meng-Tso; Lin, Yu-Feng; Liao, Li-Fen; Lien, Chen-Fu; Lin, Jong-Liang
Abstract : The adsorption, thermo- and photo-reactions ofCH 2 Br 2 on powderedTiO 2 as well as the effects ofH 2 O and/orO 2 have been studied by Fourier-transform infrared spectroscopy.CH 2 Br 2 is adsorbed molecularly on the surface at35 ∘ C, interacting with the surface OH groups. It is completely desorbed or decomposes to formCH 3 O ( a ) andHC OO ( a ) in a vacuum by250 ∘ C, probably via dioxymethylene( -OCH 2 O- ) . The presence of adsorbedH 2 O accelerates the formation ofCH 3 O ( a ) andHC OO ( a ) fromCH 2 Br 2 dissociation. AdsorbedCH 2 Br 2 decomposes to formCO ( a ), HC OO ( a ), CO 3 ( a ), and/orCO 2 ( a ) under 400 nm irradiation, depending on whether the presence ofH 2 O and/orO 2 . The presence ofO 2 increases the photoreaction rate ofCH 2 Br 2 ( a ) and the photodecomposition is further accelerated with addition ofH 2 O .